A new face for private providers in developing countries: what implications for public health? - Natasha Palmer; Anne Mills; Haroon Wadee; Lucy Gilson; Helen Schneider (Bulletin of the World Health Organization)
The use of private health care providers in low- and middle-income countries (LMICs) is widespread and is the subject of considerable debate. We review here a new model of private primary care provision emerging in South Africa, in which commercial companies provide standardized primary care services at relatively low cost. The structure and operation of one such company is described, and features of service delivery are compared with the most probable alternatives: a private general practitioner or a public sector clinic. In a case study of cost and quality of services, the clinics were popular with service users and run at a cost per visit comparable to public sector primary care clinics. However, their current role in tackling important public health problems was limited. The implications for public health policy of the emergence of this new model of private provider are discussed. It is argued that encouraging the use of such clinics by those who can afford to pay for them might not help to improve care available for the poorest population groups, which are an important priority for the government. Encouraging such providers to compete for government funding could, however, be desirable if the range of services presently offered, and those able to access them, could be broadened. However, the constraints to implementing such a system successfully are notable, and these are acknowledged. Even without such contractual arrangements, these companies provide an important lesson to the public sector that acceptability of services to users and low-cost service delivery are not incompatible objectives.